PEDAGOGICAL CONDITIONS OF MORAL EDUCATION OF GRADES 5-8 STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
We know from historical written sources that special attention is paid to the education of the next generation at any stage of society's development. To this day, the issue has not lost its relevance, but has risen to the level of public policy. At the heart of the high attention paid by the state to the upbringing of the younger generation, his education is the education of a harmoniously developed person for the development of society, raising the level of their spiritual and moral upbringing.